Anästhesie beim geriatrischen Patienten - Zink, Wolfgang (De Gruyter, 2019)
In administering anesthesia to elderly patients, there are many aspects to consider. There are significant differences in the preoperative, intraoperative, and postoperative management of geriatric patient compared to other adults. Therefore, there is a need to adhere to clear guidelines in risk assessment, managing anesthesia, and postoperative care.